Hydroxytyrosol Inhibits LPS-Induced Neuroinflammatory Responses via Suppression of TLR-4-Mediated NF-κB P65 Activation and ERK Signaling Pathway. (1st February 2020) - Zhang, Lanqiu; Zhang, Jinlu; Jiang, Xiaolin; Yang, Lei; Zhang, Qi; Wang, Botao; Cui, Lihua; Wang, Ximo
Highlights: HT reduced the production of pro-inflammatory mediators in LPS-stimulated microglia. HT reduced the expression of M1 marker CD86, while increased that of M2 marker CD206. HT inhibited the LPS-induced NF-κB activation and ERK signaling pathway in BV2 cells. In vivo administration of HT inhibited the LPS-induced neuroinflammatory responses. Abstract: Neuroinflammation has been implicated in the mechanism underlying the progression of neurodegeneration and infectious neuropathology. Growing evidence suggest that hydroxytyrosol (3, 4-dihydroxyphenil-ethanol, HT), one of the main polyphenols presented in extra virgin olive oil (EVOO), has shown potential anti-inflammatory and neuroprotective effects. However, the potential anti-neuroinflammation activity and underlying mechanism of HT remain poorly understood. The present study aimed to investigate the effects of HT on lipopolysaccharide (LPS)-induced inflammation in both in vitro and in vivo models and the associated molecular mechanism. Our results revealed that HT significantly reduced the production of pro-inflammatory mediators in BV2 microglia and primary microglia cells. Phenotypic analysis showed that HT significantly reduced M1 marker CD86 expression and increased M2 marker CD206 expression. In addition, HT significantly decreased the levels of phospho-NF-κB p65 and phospho-extracellular signal-regulated kinase (ERK) in a dose-dependent manner. Moreover, HT suppressed the LPS-induced Toll like receptor 4 (TLR4) in BV2 microglia. In vivo administration of HT following LPS injection significantly reduced some proinflammatory mediator levels and microglia/astrocyte activation in the brain. Together, these results suggest that HT suppressed the LPS-induced neuroinflammatory responses via modulation of microglia M1/M2 polarization and downregulation of TLR-4 mediated NF-κB activation and ERK signaling pathway.